Hoax News and Technology Literacy from the Qur’anic Perspective - Muhammad Yusuf, (Jurnal Komunikasi Islam, 2022)
The development of media technology and freedom of releasing news led to fake news or hoaxes spread to form a public opinion in order to get particular interests which are used to attack each other, accuse, slander, and generate stereotypes, even to claim that a specific group or religion is superior to others. This study takes under scrutiny the Qur'anic perspective about hoaxes and technology literacy to help provide context for an effort to combat fake news. Using a thematic and an anthropological approach to the Qur’an, this study has found that the Qur’an narrates that hoaxes have existed since the first humans, Adam and Eve, to test the true faith as well as pretense. The Qur’an gives a sign that the eternal enemy of honesty is a hoax. Tabayyun is a crucial concept for fighting hoaxes, and qalam is the medium.